Effects of concentration and frequency of CO2 supply on productivity of marine microalga Isochrysis galbana - Xia, Yuanjun; Sekine, Mutsumi; Hirahara, Minamo; Kishinami, Hidemi; Md. Yusoff, Fatimah; Toda, Tatsuki (Elsevier, 2023)
Demand for the high fucoxanthin and docosahexaenoic acid (DHA) content found in the marine microalga Isochrysis galbana is rising annually, and it is essential to devise large-scale cultivation systems that are low in energy and cost. Continuous CO2 supply occupies a considerable portion of total electricity consumption for microalgae cultivation. While an intermittent, high-concentration CO2 supply/agitation has the potential to reduce the electricity consumption required for aeration, it may cause carbon starvation and sedimentation of cells when the supply frequency is insufficient. This study investigated the effects of concentration and frequency of CO2 supply on productivity of I. galbana. Semi-continuous cultivation was conducted under different conditions of CO2 supply (0.04 (air) to 10 concentration and continuous or intermittent (1 min every 9 min) supply). Under continuous air supply (control), biomass productivity reached 0.18 g Lˆ’1 dayˆ’1. A continuous supply of CO2 at 5 showed the highest biomass productivity (0.33 g Lˆ’1 dayˆ’1). Productivity was only 0.12 g Lˆ’1 dayˆ’1 with a continuous CO2 supply at 10 concentration. It was confirmed that growth was suppressed under conditions of a continuous supply of CO2 at high concentrations. The study found that intermittent CO2 concentrations of 5 and 10 showed productivity of 0.29 and 0.24 g Lˆ’1 dayˆ’1, respectively. These productivities were higher than that in the control. Under conditions of continuous CO2 supply, 0.61 mg/g dry weight (DW) of a higher fucoxanthin content was achieved with air supply than was found at concentrations of 5 and 10 (0.18 and 0.11 mg/g DW, respectively). However, under intermittent supply conditions, the fucoxanthin reached the higher content of 0.56 mg/g DW under 5 supply. Under conditions of high CO2 concentrations, continuous supply inhibited the accumulation of fucoxanthin, while an intermittent supply promoted its accumulation.